Bartleby, the Scrivener : a Story of Wall-Street. - Melville, Herman, 1819-1891 (Open Road Media, 2014)
The classic tale of existential despair A Wall Street lawyer specializing in bonds and mortgages hires a respectable young man to copy legal documents by hand. At first, the new scrivener approaches his duties with a calm efficiency. Then comes the day when his response to a new assignment is, "I would prefer not to." The mysterious phrase soon becomes Bartleby's reply to everything asked of him, and his surrender to inertia is both maddening and inexorable. Torn between frustration and pity, anger and sorrow, his employer desperately tries to save Bartleby, but the cause is as doomed to disap.